GEOLOGY OF THE GRANITE ROCKS OF SGUARIO STOCK, SOUTHEAST OF SÃO PAULO STATE - Marchi, Enrico de Oliveira [UNESP] (2023)
The granitic rocks of the Sguario Stock are related to the evolution of the magmatism of the Três Córregos Granitic Batholith and conditioned the evolution of the rapakivi post-colisional granitogenesis of neoproterozoic age of the Apiaí Terrain. The rocks are located in the southwest region of the state of São Paulo, in the Ribeirão Branco municipality, intrusive in lithotypes of the metavulcanossedimentary sequence of the Água Clara Formation of the Açunguí Supergroup and in the north contact, with the metasedimentary rocks of the Itaiacoca Group. Igneous rocks are generally formed by an elliptical plúton, according to the general direction NE-SW, with an exposure of approximately 70 km2 controlled by a combination of faults imposed by the ramification Itapirapuã Shear Zone. The rocks are represented by sieno-to monzogranitic, massive varieties, predominantly the red of rosy and gray type rare, hololeucocratic, dominating the porphyritic and secondarily equi-to inequigranular types, in addition to the rocks of the late aplitic and pegmatoid phases. They present varieties with viborgitic rapakivi textures and as mafic mineral biotite dominant. The granite magmatism is associated with the transtensive structures of the shear zones at the end of the colisional event of the Ribeira Orogenesis and reflects the final geotectonic arrangement of stabilization of the Apiaí Terrain.